The clinical utility of contemporary oral epithelial dysplasia grading systems. (15th December 2021) - Sathasivam, Hans Prakash; Sloan, Philip; Thomson, Peter J.; Robinson, Max
Abstract: Introduction: Clinical management of oral potentially malignant disorders relies on accurate histopathological assessment of the presence and grade of oral epithelial dysplasia. While adjunctive laboratory tests have provided useful prognostic information, none are in widespread clinical use. This study was performed to assess the clinical utility of two contemporary oral epithelial dysplasia grading systems. Methods: Patients were identified from a clinical database. Oral epithelial dysplasia grading was performed by three oral and maxillofacial pathologists blinded to clinical outcome using the WHO 2017 system and a binary classification. The primary outcome measure was the development of oral squamous cell carcinoma, termed 'malignant transformation'. Results: One hundred thirty‐one cases satisfied the inclusion criteria, of which 23 underwent malignant transformation. There was substantial inter‐rater agreement between the study pathologists for both grading systems, measured using kappa statistics (κ = 0.753 – 0.784). However, there was only moderate agreement between the consensus WHO 2017 dysplasia grade for the study against the original grade assigned by a pool of six pathologists in the context of the clinical service (κ = 0.491). Higher grade categories correlated with an increased risk of developing cancer using both grading systems. Conclusion: This study demonstrates that the WHO 2017 and binary grading systems are reproducible between calibrated pathologists and that consensus reporting is likely to improve the consistency of grading. The WHO and binary systems were prognostically comparable. We recommend that institutions implement consensus oral epithelial dysplasia grading and prospectively audit the effectiveness of risk stratifying their patients with oral potentially malignant disorders. (249 words).